2018
DOI: 10.3390/molecules23071706
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Extraction of Polysaccharides from Volvariella volvacea: Process Optimization and Structural Characterization

Abstract: The aims of the present study were to optimize the operational parameters to maximize the yield of ultrasound-assisted polysaccharide extraction from Volvariella volvacea (straw mushroom) fruiting bodies by using for the first time one-factor-at-a-time and three-level Box-Behnken factorial designs. A maximum polysaccharide yield of 8.28 ± 0.23% was obtained under the optimized conditions of ultrasound power of 175 W, extraction temperature of 57 °C, extraction time of 33 min, and the ratio of liquid to raw mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…The maximum yield of polysaccharide (11.64%) was detected at 70℃ which a sharp declined as soon at the temperature attained 80℃. Although, some studies had suggested that a higher temperature benefit the solubility and extraction yield of polysaccharide [35] but when the temperature was above certain degree, it could decrease the polysaccharide yield of some plant materials as shown in Figure 2b. So, the temperature range of 60-80℃ was adopted as the optimal for the BBD experiment.…”
Section: Effect Of Different Temperature On the Extraction Yield Of Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum yield of polysaccharide (11.64%) was detected at 70℃ which a sharp declined as soon at the temperature attained 80℃. Although, some studies had suggested that a higher temperature benefit the solubility and extraction yield of polysaccharide [35] but when the temperature was above certain degree, it could decrease the polysaccharide yield of some plant materials as shown in Figure 2b. So, the temperature range of 60-80℃ was adopted as the optimal for the BBD experiment.…”
Section: Effect Of Different Temperature On the Extraction Yield Of Lmentioning
confidence: 99%
“…The observed functional groups of L. japonicus polysaccharide as indicated by the Fig. 6 below mainly correspond to a good source of antioxidant [35,36,[58][59][60][61][62].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…Finally, although the energy that was provided by ultrasound is necessary to release the compounds from the matrix, it may also accelerate the degradation process of the phenolic compounds [54]. In general, the action of the ultrasounds would increase the solubility of the molecules by destroying the intramolecular and intermolecular bonds and by increasing the contact between the hydrophilic groups and the extraction solvents [55]. Although it is clear that the cycle also presents an extreme value, its modification was not considered, since it was not an influential variable.…”
Section: Optimal Conditionsmentioning
confidence: 99%
“…Conclusively, this result shows that ultrasonic treatment had an insignificant effect on the chemical structure of the APS. In a previous study, Cui et al () observed unaltered chemical structures after ultrasound treatment.…”
Section: Resultsmentioning
confidence: 87%